2022
DOI: 10.1002/etc.5503
|View full text |Cite
|
Sign up to set email alerts
|

Models Used to Predict Chemical Bioaccumulation in Fish from in Vitro Biotransformation Rates Require Accurate Estimates of Blood–Water Partitioning and Chemical Volume of Distribution

Abstract: Methods for extrapolating measured in vitro intrinsic clearance to a whole-body biotransformation rate constant (k B ) have been developed to support modeled bioaccumulation assessments for fish. The inclusion of extrapolated k B values into existing bioaccumulation models improves the prediction of chemical bioconcentration factors (BCFs), but there remains a tendency for these methods to overestimate BCFs relative to measured values. Therefore, a need exists to evaluate the extrapolation procedure to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The mechanistic IVIVE models may be considered preferable from a conceptual point of view to the purely empirical regression model aimed at optimized predictivity. However, significant uncertainties in the model parameters do exist for the IVIVE models such as the volume of distribution ( V D ) and k 1 . , Until now, it has not been clear which of the IVIVE models gives the best predictivity and which should be preferred for regulatory application when using in vitro data from the OECD TG 319B. Our data provides the most comprehensive set of in vivo BCF and associated CL IN VITRO,INT data, which were generated according to the OECD TG 319B and equally the most comprehensive set of predictions using the four iterations of the IVIVE models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanistic IVIVE models may be considered preferable from a conceptual point of view to the purely empirical regression model aimed at optimized predictivity. However, significant uncertainties in the model parameters do exist for the IVIVE models such as the volume of distribution ( V D ) and k 1 . , Until now, it has not been clear which of the IVIVE models gives the best predictivity and which should be preferred for regulatory application when using in vitro data from the OECD TG 319B. Our data provides the most comprehensive set of in vivo BCF and associated CL IN VITRO,INT data, which were generated according to the OECD TG 319B and equally the most comprehensive set of predictions using the four iterations of the IVIVE models.…”
Section: Resultsmentioning
confidence: 99%
“…17 The mechanistic IVIVE models may be considered preferable from a conceptual point of view to the purely empirical regression model aimed at optimized predictivity. However, significant uncertainties in the model parameters do exist for the IVIVE models such as the volume of distribution (V D ) 52 and k 1 . 17,19 Until now, it has not been clear which of the IVIVE models gives the best predictivity and which should be preferred for regulatory application when using in vitro data from the OECD TG 319B.…”
Section: Species-matched Regressionmentioning
confidence: 99%
“…Recent work has shown that f U values can be estimated with relatively high confidence, 46,47 but there remains considerable uncertainty in the calculation of V D . 48 In particular, uncertainty in the prediction of K BW directly translates to the calculation of V D (eqn (6)) and by extension modelled k B and BCF values. The impact of this uncertainty increases with chemical K OW and is especially apparent at log K OW ≥ 6.…”
Section: Model Parameterizationmentioning
confidence: 99%
“…The impact of this uncertainty increases with chemical K OW and is especially apparent at log K OW ≥ 6. 48 Based on an evaluation of several K BW prediction models for neutral organic chemicals, Nichols et al 13 reported that existing data are best described by an empirical equation given by Fitzsimmons et al 49 For this reason, we have retained the use of empirical equations to estimate K S9W and K BW , but stress that there is a need for directed studies to evaluate K BW and V D and, if necessary, refine estimation approaches for IVIVE model partition ratios.…”
Section: Model Parameterizationmentioning
confidence: 99%
“…Alternatively, this binding may be predicted using polyparameter linear free‐energy relationships (ppLFERs; Krause & Goss, 2020). A comparison of these approaches indicates, however, that they yield different binding predictions, which translates to differences in predicted k B , and by extension the BCF (Saunders & Nichols, 2023). With only one known exception (Laue et al, 2020), all reported evaluations of the IVIVE procedure performed to date have employed binding terms estimated by one of these methods.…”
Section: Introductionmentioning
confidence: 99%